1990
DOI: 10.1007/bf02337446
|View full text |Cite
|
Sign up to set email alerts
|

24-month follow-up of multiple sclerosis patients treated with cyclophosphamide

Abstract: 15 patients with remitting-progressive multiple sclerosis received a course of intravenous cyclophosphamide followed by a booster dose every 60 days for 2 years. There were no severe short or medium term side effects. Half of the patients presented clinical stabilization and substantially unchanged Kurtzke rating at 2 year follow-up. Since the aim was stabilization only, our findings argue for continuation of the study in young patients with very short shift.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…69 Killian et al treated 14 relapsingremitting patients with monthly pulses of 750 mg/m 2 for 1 year in a pilot randomized, double-blind placebo-controlled trial that showed a positive trend ( p= 0.06) in 6 treated versus 8 placebo patients. 52 D'Andrea et al treated seven relapsing-remitting patients with every 6-month pulses after induction 53 and Millefiorini et al treated 15 remitting-progressive patients with every 2 month boosters for 2 years after IV induction 54 and both reported positive effects in open-label trials. La Mantia et al reported in 30 progressive patients a better response in relapsing-progressive patients and in those receiving induction plus boosters (600 mg/m 2 ) every 2 months for 12 months.…”
Section: The Canadian Cooperative Study and The Kaiser Studymentioning
confidence: 99%
“…69 Killian et al treated 14 relapsingremitting patients with monthly pulses of 750 mg/m 2 for 1 year in a pilot randomized, double-blind placebo-controlled trial that showed a positive trend ( p= 0.06) in 6 treated versus 8 placebo patients. 52 D'Andrea et al treated seven relapsing-remitting patients with every 6-month pulses after induction 53 and Millefiorini et al treated 15 remitting-progressive patients with every 2 month boosters for 2 years after IV induction 54 and both reported positive effects in open-label trials. La Mantia et al reported in 30 progressive patients a better response in relapsing-progressive patients and in those receiving induction plus boosters (600 mg/m 2 ) every 2 months for 12 months.…”
Section: The Canadian Cooperative Study and The Kaiser Studymentioning
confidence: 99%